microRNA regulation of skin pigmentation in golden-back mutant of crucian carp from a rice-fish integrated farming system - Xianbo Zhang; Mingkun Luo; Bingjie Jiang; Wenbin Zhu; Qianwen Min; Jinli Hu; Ting Liu; Jianjun Fu; Xiulan Shi; Pan Wang; Lanmei Wang; Zaijie Dong (BMC Genomics, 2023)
Abstract Background MicroRNAs (miRNAs) are endogenous small non-coding RNAs (21–25 nucleotides) that act as essential components of several biological processes. Golden-back crucian carp (GBCrC, Carassius auratus) is a naturally mutant species of carp that has two distinct body skin color types (golden and greenish-grey), making it an excellent model for research on the genetic basis of pigmentation. Here, we performed small RNA (sRNA) analysis on the two different skin colors via Illumina sequencing. Results A total of 679 known miRNAs and 254 novel miRNAs were identified, of which 32 were detected as miRNAs with significant differential expression (DEMs). 23,577 genes were projected to be the targets of 32 DEMs, primarily those involved in melanogenesis, adrenergic signaling in cardiomyocytes, MAPK signaling pathway and wnt signaling pathway by functional enrichment. Furthermore, we built an interaction module of mRNAs, proteins and miRNAs based on 10 up-regulated and 13 down-regulated miRNAs in golden skin. In addition to transcriptional destabilization and translational suppression, we discovered that miRNAs and their target genes were expressed in the same trend at both the transcriptional and translational levels. Finally, we discovered that miR-196d could be indirectly implicated in regulating melanocyte synthesis and motility in the skin by targeting to myh7 (myosin-7) gene through the luciferase reporter assay, antagomir silencing in vivo and qRT-PCR techniques. Conclusions Our study gives a systematic examination of the miRNA profiles expressed in the skin of GBCrC, assisting in the comprehension of the intricate molecular regulation of body color polymorphism and providing insights for C. auratus breeding research.